Changing the Culture of Teaching and Learning in ICT and Engineering : Facilitating Research Professors to be Teaching and Learning Leaders : Final Report. - Edwards, Sylvia; Narayan, Bhuva; Sheard, Judithe; O'Shea, Peter; Brookes, Wayne (Office for Learning and Teaching, 2012)
Final report of a Teaching Fellowship at the Queensland University of Technology. This project aimed to build teaching leadership within the higher education sector by working with established leadership in the higher degree research domain, namely the professoriate. The development of teaching and learning (T&L) leadership "from scratch" is problematic and it is more promising to transfer skills that already exist in a context. In Australian universities there are many professors who have been promoted because of their leadership in research (rather than teaching) and these professors have developed valuable leadership skills in their roles. The professors have much to offer in T&L leadership, and this project set out to tap this potential. Because this project focused on increasing the engagement of the Australian professoriate in T&L leadership, it gave much needed attention to the "research-teaching nexus". In so doing it promoted more balanced and effective leadership within the higher educational sector. Specific project objectives were to: to build leadership capacity in teaching and learning, and to improve teaching quality in ICT and Engineering disciplines at three leading Australian universities; and to facilitate the transference of research leadership to T&L leadership, and disseminate this transference model developed through the project within the Engineering and ICT domains to other disciplines and universities.